Novel aspects of platelet aggregation - Roka-Moya, Y.M.; Bilous, V.L.; Zhernossekov, D.D.; Grinenko, T.V. (Вiopolymers and Cell, 2014)
The platelet aggregation is an important process, which is critical for the hemostatic plug formation and thrombosis. Recent studies have shown that the platelet aggregation is more complex and dynamic than it was previously thought. There are several mechanisms that can initiate the platelet aggregation and each of them operates under specific conditions in vivo. At the same time, the influence of certain plasma proteins on this process should be considered. This review intends to summarize the recent data concerning the adhesive molecules and their receptors, which provide the platelet aggregation under different conditions.